Canada. Significant achievements 2013 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Canada during 2013 are identified, with respect to the needs and interests of the country, strengthening issues such as innovation, productivity and research. Finally, technical assistance was provided in the management of agroforestry resources, dairy production and in the value chains of small ruminants, such as goats.